2013
DOI: 10.1039/c3lc50178g
|View full text |Cite
|
Sign up to set email alerts
|

Dissolvable fluidic time delays for programming multi-step assays in instrument-free paper diagnostics

Abstract: Lateral flow tests (LFTs) are an ingenious format for rapid and easy-to-use diagnostics, but they are fundamentally limited to assay chemistries that can be reduced to a single chemical step. In contrast, most laboratory diagnostic assays rely on multiple timed steps carried out by a human or a machine. Here, we use dissolvable sugar applied to paper to create programmable flow delays and present a paper network topology that uses these time delays to program automated multi-step fluidic protocols. Solutions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
214
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(215 citation statements)
references
References 41 publications
1
214
0
Order By: Relevance
“…For example, paperbased device's channel widths and fluid path lengths were configured to program delivery sequence; 7,8 multiple pads were arranged in specific orientation; 6,9,10 electromagnet and fluidic diodes were used for timed valving; 11,12 paper channel was sandwiched between two films to increase the velocity in the channel; 13 and dissolvable barriers were applied for fluidic delays. 14,15 However, increasing the width or fluidic path length to decrease flow velocity can result in increased sample consumption and may not be appropriate when dealing with small volume samples such as blood. Moreover, adding multiple pads, installing fluidic valves, covering films over channels, and applying dissolvable barriers resulted in complicated manufacturing processes of paper fluidic devices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, paperbased device's channel widths and fluid path lengths were configured to program delivery sequence; 7,8 multiple pads were arranged in specific orientation; 6,9,10 electromagnet and fluidic diodes were used for timed valving; 11,12 paper channel was sandwiched between two films to increase the velocity in the channel; 13 and dissolvable barriers were applied for fluidic delays. 14,15 However, increasing the width or fluidic path length to decrease flow velocity can result in increased sample consumption and may not be appropriate when dealing with small volume samples such as blood. Moreover, adding multiple pads, installing fluidic valves, covering films over channels, and applying dissolvable barriers resulted in complicated manufacturing processes of paper fluidic devices.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of paper wicking in multidimensional channels clamped by paper pins also complied with the Washburn equation. 20,23 A separate experiment revealed that reproducibility was minimally affected by the pins. An orange dye solution was distributed on 16 test zones, and the signal intensity was measured by the homemade paper-based colorimetric readout device 8 (displayed in Figure S4).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…In recent years the subject has been re-visited and expanded (Martinez et al, 2008b(Martinez et al, , 2010Noh et al, 2010;Lutz et al, 2013;Byrnes et al, 2013). Autonomous capillary systems can also be implemented using micro fabrication techniques rather than paper, which offer the benefits of compatibility with classical LOC architectures and the use of detection principles beyond colorimetry (Zimmermann et al, 2007;Gervais and Delamarche, 2009;Safavieha and Juncker, 2013).…”
Section: Transport / Reactionmentioning
confidence: 99%